2023
DOI: 10.1038/s41433-023-02500-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and management of Demodex blepharitis: the Demodex Expert Panel on Treatment and Eyelid Health (DEPTH)

Abstract: Background Twelve ocular surface disease experts convened to achieve consensus about Demodex blepharitis (DB) using a modified Delphi panel process. Methods Online surveys were administered using scaled, open-ended, true/false, and multiple-choice questions. Consensus for questions using a 1 to 9 Likert scale was predefined as median scores of 7–9 and 1–3. For other question types, consensus was achieved when 8 of 12 panellists agreed. Questions were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Demodex mites have been implicated in rosacea and there are close associations between Demodex skin infestation and ocular Demodex. 34,35 It is believed that once facial demodicosis develops, Demodex mites migrate and flourish around the eyes as well, contributing to ocular rosacea and/or Demodex blepharitis. Ocular rosacea is characterized by telangiectasia, lid margin irregularity, and meibomian gland dysfunction; ocular rosacea can lead to severe ocular surface disease, including cicatrizing conjunctivitis and corneal perforation.…”
Section: Rosaceamentioning
confidence: 99%
See 3 more Smart Citations
“…Demodex mites have been implicated in rosacea and there are close associations between Demodex skin infestation and ocular Demodex. 34,35 It is believed that once facial demodicosis develops, Demodex mites migrate and flourish around the eyes as well, contributing to ocular rosacea and/or Demodex blepharitis. Ocular rosacea is characterized by telangiectasia, lid margin irregularity, and meibomian gland dysfunction; ocular rosacea can lead to severe ocular surface disease, including cicatrizing conjunctivitis and corneal perforation.…”
Section: Rosaceamentioning
confidence: 99%
“…Collarettes-solidified exudative excretions that form a cylindrical collar around the base of the eyelash follicle-are the pathognomonic sign of Demodex blepharitis. 18,21,24,35,39,[45][46][47][48][49] Several robust studies have shown that all eyes with collarettes (100%) are positive for Demodex mites, identified by microscopy 48 or by polymerase chain reaction genetic testing for the mite DNA. 12 Often referred to in the literature as cylindrical dandruff (CD), collarettes have also been called sleeves, cuffs, crusting, or lash debris.…”
Section: Diagnosis Of Demodex Blepharitis Clinical Signsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many questions remain unanswered, including why there is poor correlation between symptoms and objective signs of DB. In this issue of Eye, experts on the Demodex Expert Panel on Treatment and Eyelid Health (DEPTH) panel attempt to achieve consensus regarding the symptoms and diagnosis of DB [9]. Consensus was reached on several points.…”
mentioning
confidence: 99%